Strengthening Business Law in Maritime Integration for Procompetitive Port Governance - Ryan Rudyarta; Dodi Sugianto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The role of ports as crucial nodes in the global supply chain positions the maritime sector as one of the most dynamic industries worldwide. This research analyzes the strengthening of business law support maritime sector integration to enhance port operational efficiency and the role of business law instruments in realizing the principle of fair competition within ports. This research employs a normative legal approach focusing on the study of existing legal norms and regulations governing port management and maritime integration. The strengthening of business law in the maritime sector plays a crucial role in improving port operational efficiency. A strong and well coordinated business law framework will create ports that are more efficient, competitive, and adaptive to the changing demands of the global market. Several key principles must be developed. First, rules on information disclosure and accountability to ensure transparency in port governance. Second, prohibitions against abuse of dominant positions and oversight of vertical integration to prevent anti-competitive practices. Third, clear contractual norms and governance structures for public private partnerships (PPP), including proportional risk-sharing mechanisms to ensure fairness and efficiency in infrastructure development. Fourth, multi-level governance alignment across national and regional authorities to prevent incentive distortions.